FILSAFAT KEBUDAYAAN DAN SASTRA (DALAM PERSPEKTIF SEJARAH) - Teng, H. Muhammad Bahar Akkase (JURNAL ILMU BUDAYA, 2017)
This paper addresses about philosophy, culture, and literature from a historical perspective. Philosophy is one of the discipline in which some interrelated disciplines of the world derive, such as education. Philosophy is concerned with how human think but not all thingking processes constitute philosophy. Indulging in philosophy implies deep and serious thingking. Cultural philosophy has uniqueness because some of its explanation involves other interrelated disciplines, such as historical philosophy, anthropology, sociology, and psychology. Cultural philosophy attempts to explain cultural element and their underlying rules, structures, and their accompanying values. Despite its emergence in the twentieth century, it has rooted since Socratic era even before. Culture is men’s product during his life that does not stop there. When a culture of human being ceases to develop at certain point, it will become a civilization. Contemporary culture is influenced by rapid development and modern man is well aware of it. Culture constitutes a literary work of an individual and the object of a literary work concerns culture and social life of a community. A Literary work is never created from void.Key Words : philoshopy, culture, literary and a historical